Water replenishment on soil and impact of foliary diseases on feijoeiro cultivars (phaseolus vulgaris L.) - Valeriano, Taynara Tuany Borges [UNESP]; Oliveira, Ana Flávia; DE SANTANA, Márcio José; DE PAIVA, Isaías Antonio; Amaral, E Daniel Rufino (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2018)
The incidence of foliar diseases is one of the main factors that interfere with yield and is directly related to the water depths applied in bean crop. The objective of this work was to evaluate the effect of soil water replenishment on foliar diseases incommon bean cultivars. The experiment was conducted in a greenhouse located at the Instituto Federal do Triângulo Mineiro (IFTM Campus-Uberaba). The experimental design was randomized blocks with five replications, arranged in a 2x5 factorial arrangement, two cultivars, IAC Imperador and IPR Juriti, five replenishments of soil water, 40%, 60%, 80%, 100% and 120% of crop evapotranspiration, and five water replacements. Diseases evaluated were common bacterial blight and alternaria spot in the 10-day interval. The irrigation management was carried out by the method of percolating water collection drains. Depth corresponding to 100% and 120% ETC showed higher severity of alternaria and common bacterial blight to cultivar IPR Juriti. There was linear and quadratic increase of ASCPD for common bacterial blight and alternaria spot, respectively, with increased depth. The highest productivity values of common bean, as well as greater efficiency in water use, were obtained with depth of approximately 80% of the ETC.
Reposições de água no solo e incidência de doenças foliares em cultivares de feijoeiro (Phaseolus vulgaris L.)
Keywords: Alternaria spot; Bacterial blight; Evapotranspiration; Plant pathology